Realizing Recognition Justice in Flood Risk Management Policy: A Case Study on Implementation Gaps and Legitimacy Gaps in Austria - Thomas Thaler; Sebastian Seebauer (Journal of Flood Risk Management, 2025)
ABSTRACT Flood risk is often unequally distributed. These inequalities highly depend on socio‐political decisions. The recognition of the needs of individuals within a floodplain needs to be considered as a precondition for reaching justice in flood risk management, especially as people differ in their vulnerabilities and capacities to deal with floods. This paper addresses the question of how vulnerable population groups are recognized in flood risk management used in the federal state of Upper Austria. We use a qualitative research method, which is based on policy, legal documents and strategies and on 32 semi‐structured interviews conducted at different levels. Even though clearly stating the overall policy goal of reducing social vulnerability and inequality, most risk reduction strategies neglect these aspects, which creates an implementation gap regarding recognition justice. Strict adherence to the principle of equality leads to, among others, uniform design levels and cost contributions that undermine the notion of differentiated vulnerability. By contrast, disaster aid payments do use eligibility criteria that recognize social inequalities. However, even if justice principles are implemented, they lack transparency and accountability, which creates a legitimacy gap. Restricting the role of civil servants in the public administration through hybrid governance may narrow implementation and legitimacy gaps.